Pelatihan Digital Marketing Dan Pembuatan Media Pemasaran Digital Pada UMKM YW Label - Muhamad Brilliant; Iis Ariska Nurhasanah; Nizamiyati (PT. Karya Inovatif Nusantara, 2024)
This community service initiative aims to enhance digital marketing and business sustainability for Micro, Small, and Medium Enterprises (MSMEs) Yasmin Wiwid Label. Through a collaborative effort between the Diniyyah Lampung Institute of Technology and Business and MSME Yasmin Wiwid Label, the project focuses on providing digital marketing training and developing a dedicated website landing page. The training equips MSMEs with new knowledge and skills to independently manage digital marketing efforts, while the website landing page is designed to improve their online presence. The initiative seeks to broaden MSMEs' marketing reach, boost sales conversion, and foster sustainable business growth. Further evaluation and ongoing strategy development are recommended to maximize the impact of this community service endeavor